Canadian Educators’ Narratives of Teaching Multicultural Education - Syed, Khalida (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This article describes the challenges and accomplishments of teaching multicultural education in graduate courses at Canadian universities. Critics of current multicultural education have focused on creating a multicultural curriculum from culturally diverse literary sources and teaching methods. My focus has been to ask educators, through narrative inquiry, about critical aspects of their experiences of designing and teaching a multicultural curriculum. Multiculturalism is no longer a concern of minorities and immigrants; it has become a social issue of concern to all. The insights and knowledge gained from this research may guide policy makers and educators to understand and address the ever-changing characteristics of multiculturalism in order to live in a harmonious society.